ӘДЕБИЙ-ИЛИМИЙ ҲҮЖДАН ҲӘМ ҲУҚЫҚЫЙ ТӘРБИЯ МӘСЕЛЕЛЕРИ - Алламбергенов, Е.К. (FAN va JAMIYAT, 2016)
The article deals with the role of legal education in the development of scientific and literary conscicusness in the students of schools, secondary special professional and higher educational establishments in the system of continuous education.